Complement C3a receptor inactivation attenuates retinal degeneration induced by oxidative damage - Wang, Shaojun; Du, Lu; Yuan, Shunzong; Peng, Guang-Hua (Frontiers in Neuroscience, 2022)
Retinal degeneration causes vision loss and threatens the health of elderly individuals worldwide. Evidence indicates that the activation of the complement system is associated with retinal degeneration. However, the mechanism of complement signaling in retinal degeneration needs to be further studied. In this study, we show that the expression of C3 and C3a receptor (C3ar1) is positively associated with the inflammatory response and retinal degeneration. Genetic deletion of C3 and pharmacological inhibition of C3ar1 resulted in the alleviation of neuroinflammation, prevention of photoreceptor cell apoptosis and restoration of visual function. RNA sequencing identified a C3ar1-dependent network shown to regulate microglial activation and astrocyte gliosis formation. Mechanistically, we found that STAT3 functioned downstream of the C3-C3ar1 pathway and that the C3ar1-STAT3 pathway functionally mediated the immune response and photoreceptor cell degeneration in response to oxidative stress. These findings reveal an important role of C3ar1 in oxidative-induced retinal degeneration and suggest that intervention of the C3ar1 pathway may alleviate retinal degeneration.